Eksplorasi Jamur Desa Tulung Agung, Lampung Timur dan Potensi Pemanfaatannya - Sari, Okta Yulia; Mahardhika, Wahyu Aji; Afsari, Nadhila Mutia; Putra, Ivan Permana (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2022)
Mushrooms an be found in various places, such as litter, rotten wood, trees, and soil around residential areas. Tulung Agung Village in East Lampung Regency has various kinds of vegetation and several other abiotic factors that support the growth of mushroom. The study of mushroom’s exploration could elaborate the knowledge about mushroom diversity in resdential areas. This study aims to explore the types of mushrooms based on the description of their fruiting bodies from the residential location of Tulung Agung Village, District Pekalongan, East Lampung Regency, Lampung. The methods used were purposive sampling technique in a shady area or under the shade of a tree, documenting the mushroom fruiting bodies hat were found, and presenting mushrooms with fruiting bodies characters. After the exploration, 18 species from 14 genera of mushrooms were found, including Auricularia auricula-judae, Collybia sp., Conocybe sp., Daldinia sp., Gymnopilus sp., Marasmius sp., Marasmius haematocephalus, Mycena sp., Lepiota sp., Parasola sp., Pycnoporus sp., Trametes sp., Tremellodendron sp., and Xylaria sp. The various potentials of each type of mushrooms that were found are for food sources, traditional medicines, biodegradation of contaminants, sources of bioluminescence, and sources of various bioactive compounds. The Mushroom that were found need molecular identification to get the correct species so that the potential of Mushroom can be utilized optimally by residents based on more specific type information.